Failure of Sequential Pallidal and Motor Thalamus DBS for Rapid‐Onset Dystonia‐Parkinsonism (DYT12). Issue 4 (4th December 2017) - Fearon, Conor; McKinley, John; McCarthy, Allan; Rebelo, Pedro; Goggin, Carole; Magennis, Brian; Aziz, Tipu; Green, Alexander L.; Lynch, Timothy
Abstract : View Supplementary Video 1